The Effect of Counter Electrode Preparation Methods Toward Dye Sensitized Solar Cell Performance - Pramujo Widiatmoko; Hary Devianto; Isdiriayani Nurdin; Adriaan Adriaan; Henry Natanail Purwito (Jurnal Teknologi Bahan dan Barang Teknik, 2018)
Carbon-coated electrodes is superior substitution for platinum electrodes of Dye-Sensitized Solar Cells (DSSC). This paper describes effect of electrode coating methods as well as carbon types on the performance of DSSC. The electrodes were prepared using 3 methods, i.e. doctor blade, metering rod and bubble deposition. Commercial industrial-grade and medical-grade activated carbon were used in this research. The DSSC performance was measured from I-V curve and electrochemical impedance spectroscopy, meanwhile the morphology of coated carbon electrode was studied from Scanning Electron Microscope and Brunauer-Emmett-Teller analysis. It was found that efficiency of DSSC was higher when the counter electrodes were prepared using doctor blade and bubble deposition methods with medical-grade activated carbon. The highest achievement on light-to-electricity conversion was 3.76%.Elektroda bantu karbon merupakan alternatif pengganti elektroda platinum yang baik untuk aplikasi sel surya tersensitisasi pewarna (Dye-Sensitized Solar Cell, DSSC). Makalah ini menjelaskan pengaruh metode pelapisan elektroda bantu serta jenis karbon pada kinerja DSSC. Elektroda disiapkan menggunakan 3 metode yaitu bilah dokter, batang pengaduk dan pelapisan gelembung. Karbon aktif untuk industri dan medis digunakan dalam penelitian ini. Kinerja DSSC ditentukan berdasarkan data kurva I-V dan spektroskopi impedansi elektrokimia, sementara morfologi lapisan karbon pada elektroda dipelajari menggunakan Scanning Electron Microscope dan analisis Brunauer-Emmett-Teller. Efisiensi DSSC lebih tinggi diperoleh ketika elektroda bantu disiapkan menggunakan metode bilah dokter dan pelapisan gelembung dengan karbon aktif medis. Perolehan tertinggi efisiensi konversi cahaya ke listrik adalah 3,76%.